Climate change perception and adaptation among indigenous farmers : A study on Thamis of Dolkha - Thapa, B. J. (Banko Janakari, 2019)
Anthropogenic climate change is perceived as one of the most threatening global environmental issues today. A common finding in the past researches is that most of the vulnerable communities affected by the changing climate are the indigenous ones living in rural parts of the world, mostly from the developing nations. These indigenous communities have a close relation with their surrounding environments which have provided them a vast knowledge and clues about the micro-climatic conditions in their surroundings. These clues shape their perceptions and adaptation practices. This research was conducted on the indigenous Thami Community of Nepal focusing on their perceptions towards changing climate and their adaptation practices in congruence with their local and indigenous knowledge about their environment. As Thamis are mostly reliant on subsistence agricultural farming for their livelihood, this study mainly focuses on the impacts of climate change on agriculture practices of Thami Community of Dolakha district. In this study it was found that the practices of Thamis were severely affected by the changing environmental conditions. The farmers perceived changes in temperatures, precipitation and extreme weather events, and interpreted those as per their understanding of their surroundings